Sistem Pengelolaan Sampah Medis Di RSIA Nun Surabaya Tahun 2021 - Muhammad Syahrul Rizal; Marlik Marlik; Darjati Darjati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
RSIA NUN Surabaya is a type C private hospital ‘in the ‘field of ‘maternal and ‘child ‘health. Hospitals produce infectious medical waste. In the medical waste management process, there has been a buildup of medical waste at TPS, there is no special route for waste transportation and the use of PPE by waste management officers is not appropriate. The ‘purpose ‘of ‘this study was to determine ‘the ‘medical waste ‘management ‘system ‘at RSIA NUN Surabaya. This ‘type ‘of research is a ‘descriptive observasional ‘research. ‘Data ‘collection was carried out by assessing the medical waste management process, interviews with the head of the sanitation installation and medical waste management officers. The assessment will be compared with Permenkes No. 7 of 2019 concerning Hospital Environmental Health. RSIA NUN Surabaya produces medical waste of 14.29 kg/day. The medical waste management process at the stage of sorting and collecting has been very good with a percentage of 100%. At the transportation stage, it is included in the poor category with a percentage of 64% because there are several components that are not available. At the temporary shelter it is good with a percentage of 80%. The ‘conclusion ‘of this ‘study is ‘that ‘the ‘medical waste management process at RSIA NUN Surabaya is very good and in accordance with Permenkes No. 7 of 2019. In this case the hospital needs to make improvements by fulfilling supporting facilities and infrastructure and providing training to medical waste officers so that medical waste management is carried out well.